Plan integral de marketing deportivo para fomentar el desarrollo del ecuavoley en el sector norte de Quito. - Luna Paredes, Verónica Yadira (2014)
This thesis has been developed because the ecuavoley is a native sport that is slowly losing in Ecuador, maybe the lack of support from institutions such as the Ministry of Sports has been contributing to the continuing decline of players and fans, for this reason we have developed a "Integral plan of marketing sport to promote the development of ecuavoley in the north sector of Quito”, leading to improvement and promotion of the sport. The main problem of the ecuavoley is the lack of a control body to plan, organize and regulate the sport, which has led to a lack of both amateurs and athletes, which is why it has been proposed that this research topic.